Regional‐scale measurements of CH 4 exchange from a tall tower over a mixed temperate/boreal lowland and wetland forest - Cindy Werner; Kenneth Davis; Peter Bakwin; Chuixiang Yi; Dale Hurst; Loreen Lock (Global Change Biology, 2003)
The biosphere–atmosphere exchange of methane (CH 4 ) was estimated for a temperate/boreal lowland and wetland forest ecosystem in northern Wisconsin for 1997–1999 using the modified Bowen ratio (MBR) method. Gradients of CH 4 and CO 2 and CO 2 flux were measured on the 447‐m WLEF‐TV tower as part of the Chequamegon Ecosystem–Atmosphere Study (ChEAS). No systematic diurnal variability was observed in regional CH 4 fluxes measured using the MBR method. In all 3 years, regional CH 4 emissions reached maximum values during June–August (24±14.4 mg m −2 day −1 ), coinciding with periods of maximum soil temperatures. In 1997 and 1998, the onset in CH 4 emission was coincident with increases in ground temperatures following the melting of the snow cover. The onset of emission in 1999 lagged 100 days behind the 1997 and 1998 onsets, and was likely related to postdrought recovery of the regional water table to typical levels. The net regional emissions were 3.0, 3.1, and 2.1 g CH 4 m −2 for 1997, 1998, and 1999, respectively. Annual emissions for wetland regions within the source area (28% of the land area) were 13.2, 13.8, and 10.3 g CH 4 m −2 assuming moderate rates of oxidation of CH 4 in upland regions in 1997, 1998, and 1999, respectively. Scaling these measurements to the Chequamegon Ecosystem (CNNF) and comparing with average wetland emissions between 40°N and 50°N suggests that wetlands in the CNNF emit approximately 40% less than average wetlands at this latitude. Differences in mean monthly air temperatures did not affect the magnitude of CH 4 emissions; however, reduced precipitation and water table levels suppressed CH 4 emission during 1999, suggesting that long‐term climatic changes that reduce the water table will likely transform this landscape to a reduced source or possibly a sink for atmospheric CH 4 .